Functional large-conductance calcium and voltage-gated potassium channels in extracellular vesicles act as gatekeepers of structural and functional integrity - Shridhar Sanghvi; Divya Sridharan; Parker Evans; Julie Dougherty; Kalina Szteyn; Denis Gabrilovich; Mayukha Dyta; Jessica Weist; Sandrine V. Pierre; Shubha Gururaja Rao; Dan R. Halm; Tingting Chen; et al. (Nature Communications, 2025)
Abstract Extracellular vesicles (EVs) are associated with intercellular communications, immune responses, viral pathogenicity, cardiovascular diseases, neurological disorders, and cancer progression. EVs deliver proteins, metabolites, and nucleic acids into recipient cells to effectively alter their physiological and biological response. During their transportation from the donor to the recipient cell EVs face differential ionic concentrations, which can be detrimental to their integrity and impact their cargo content. EVs are known to possess ion channels and transporters in their membrane but neither the function nor the role of these channels in EVs is known. In this study, we discover a functional calcium-activated large-conductance potassium channel (BKCa) in the membrane of EVs. Furthermore, we establish that BKCa is essential for the structural and functional integrity of EVs. Together, these findings establish the critical role of ion channels such as BKCa in functioning as gatekeepers and maintaining EV-mediated signaling.